The Effect of Myopia on Brain Signals: Insights from EEG Studies - Gani, Ernawatil; Rio, Afrioni Roma; Nugraha, Mahendra Kusuma; Haryanto, Freddy (Universitas Negeri Surabaya, 2024)
Refractive vision disorders, such as myopia, can significantly influence an individual's cognitive performance, particularly their ability to perceive and interpret visual stimuli. Myopia, a common refractive error affecting children and adults, can be assessed using various methods, including electroencephalography (EEG). The primary objective of this investigation was to identify distinctive brain signals associated with myopia. This study delves into analyzing brain signals in myopic individuals by employing EEG data and spectral entropy analysis through MNE-Python. EEG data were collected from five myopic participants during a 10-minute session, both with and without their corrective glasses. The collected data underwent preprocessing and power spectral density calculations. Subsequently, spectral entropy analysis was employed to assess the complexity and distribution skewness of EEG frequency patterns. The results of this study revealed notable differences in brain activity, particularly in the occipital region, between individuals wearing glasses and those without them. This variance could be attributed to the enhanced visual clarity experienced by individuals wearing glasses, enabling them to perceive better and process the visual stimuli presented in the study videos. Specifically, spectral entropy values were lower in children without glasses (averaging 1.0) than those with glasses (averaging 3.5), indicating a higher degree of irregularity in the brain activity of myopic children who do not wear corrective eyewear. In conclusion, this study indicates an increase in brain activity irregularities among children without glasses. The findings suggest that specific factors, such as blinking and hand movements, play a role in exacerbating this irregularity. These findings reveal how myopia affects brainwave patterns and indicate that EEG and spectral entropy analysis can enhance our understanding of refractive vision disorders.